FPGA-based algorithms for the new trigger system for the phase 2 upgrade of the CMS drift tubes detector - Cela-Ruiz, J.-M. (Journal of instrumentation, 2017)
The new luminosity conditions imposed after the LHC upgrade will require a dedicated upgrade of several subdetectors. To cope with the new requirements, CMS drift tubes subdetector electronics will be redesigned in order to achieve the new foreseen response speed. In particular, it is necessary to enhance the first stage of the trigger system (L1A). In this document we present the development of a software algorithm, based on the mean timer paradigm, capable of reconstructing muon trajectories and rejecting spurious signals. It has been initially written in C++ programming language, but designed with its portability to a FPGA VHDL code in mind.